2013
DOI: 10.1016/j.jtcvs.2012.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of recurrence and second primary lung cancer in early-stage lung cancer survivors followed with routine computed tomography surveillance

Abstract: Almost all second primary cancers and the majority of recurrences were detected by post-therapeutic surveillance computed tomography scan. The risk of recurrence for early-stage non-small cell lung cancer survivors persisted during the first 4 years after resection, and vigilance in surveillance should be maintained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
181
2
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(203 citation statements)
references
References 15 publications
11
181
2
9
Order By: Relevance
“…23 After both surgery and SABR, an early manifestation of distant metastases represents the predominant pattern of disease failure. 6,13 The present finding that overall survival is correlated only with the Charlson Comorbidity Index is consistent with population-based data indicating that stage-specific 5-year survival rates in the Danish Lung Cancer Registry for patients with earlystage NSCLC and severe comorbidity were significantly lower than in patients without comorbid disease, with the survival impact of severe comorbidity found to be greatest during the first month after surgery, but persisting during long-term follow-up. 24 The findings of all these studies will add to clinical equipoise and should encourage enrollment in randomized clinical trials to better compare the effectiveness of surgery and SABR in patients with early-stage NSCLC.…”
supporting
confidence: 89%
“…23 After both surgery and SABR, an early manifestation of distant metastases represents the predominant pattern of disease failure. 6,13 The present finding that overall survival is correlated only with the Charlson Comorbidity Index is consistent with population-based data indicating that stage-specific 5-year survival rates in the Danish Lung Cancer Registry for patients with earlystage NSCLC and severe comorbidity were significantly lower than in patients without comorbid disease, with the survival impact of severe comorbidity found to be greatest during the first month after surgery, but persisting during long-term follow-up. 24 The findings of all these studies will add to clinical equipoise and should encourage enrollment in randomized clinical trials to better compare the effectiveness of surgery and SABR in patients with early-stage NSCLC.…”
supporting
confidence: 89%
“…However, 20-30% of early stage NSCLC patients undergo a relapse even upon complete surgical resection of their tumor (32,33). Platinum-based adjuvant chemotherapy for NSCLC patients with stage IB-IIIA disease has been investigated in several clinical trials (34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…CT evaluation of response to treatment is usually dependent on morphologic changes in tumor and nodes. Lou et al [34] showed that CT detected 93% of new lung cancers and 61% of recurrences in a cohort of over 1000 patients after resection of earlystage non-small-cell lung cancer (NSCLC). Despite these results, there is currently no consensus on the optimal follow-up and surveillance program for patients with proven lung cancers.…”
Section: Screening For Lung Cancermentioning
confidence: 99%